2017
DOI: 10.1016/j.sna.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

A real-time wearable emotion detection headband based on EEG measurement

Abstract: A real-time emotion detection system based on electroencephalogram (EEG) measurement has been realised by means of an emotion detection headband coupled with printed signal acquisition electrodes and open source signal processing software (OpenViBE). Positive and negative emotions are the states classified and the Theta, Alpha, Beta and Gamma frequency bands are selected for the signal processing. It is found that, by using a combination of Power Spectral Density (PSD), Signal Power (SP) and Common Spatial Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Scalp-based emotion classification by multi-channel EEG has been an active field of research [1,7,8,9,10,11,12,13,14,15,16]. A review of some of those works can be found in [7].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Scalp-based emotion classification by multi-channel EEG has been an active field of research [1,7,8,9,10,11,12,13,14,15,16]. A review of some of those works can be found in [7].…”
Section: Related Workmentioning
confidence: 99%
“…Other areas of focus for scalp-based EEG emotion classification include those in [15,27], which look to develop wearable headband solutions. However, for monitoring purposes, these designs may suffer in conditions such as a warm climate; it might be uncomfortable to wear headband for a long duration due to sweating.…”
Section: Related Workmentioning
confidence: 99%
“…Examples of these rating scales are the Bivariate Evaluation and Ambivalent Measures (BEAM), described in [18] and the three-dimensional space proposed in [19], which distinguishes between tension arousal and energy arousal. Emotional map from [13], adapted with permission.…”
Section: Figurementioning
confidence: 99%
“…After the stimulus onset, Wei defines a time range of [0.5-4] s as the temporal space in which emotional signals appear [13]. This period has been divided by some authors into three sections: Early [400-1100] ms, Middle [1000-3000] ms, Late [3000-5000] ms [32].…”
Section: Timingmentioning
confidence: 99%
“…There are increasing levels of research activity focusing on integrating dry electrodes into textiles for wearable healthcare applications. However, most applications focus on diagnostics and monitoring such as ECG [ 14 , 15 ], EEG [ 16 , 17 ] and EMG [ 18 , 19 ]. Their application in therapeutics is limited mainly due to the issue of discomfort caused by the high impedance between the dry electrode and skin [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%